Bronchography in the assessment of patients with lung collapse for endoscopic laser therapy. Issue 7 (July 1990) - George, P J; Pearson, M C; Edwards, D; Rudd, R M; Hetzel, M R
Abstract : In an attempt to improve selection of patients and the efficacy of endoscopic laser treatment, a bronchographic technique has been developed for patients with tumours causing complete endobronchial obstruction. This technique has shown patent distal airways in 16 out of 17 patients with a collapsed lung or lobe. These airways were abnormally dilated in each case, suggesting bronchiectasis. In one patient the appearances of bronchiectasis were sufficiently severe to decide against attempting treatment. Treatment was not attempted in another patient as a large cavity was seen within the collapsed lung and this was thought to carry a risk of postoperative infection and haemorrhage. Treatment with a neodymium YAG laser under general anaesthesia successfully recanalised the airway in 12 of the 15 remaining patients and was associated with a substantial reduction in breathlessness. The procedure was abandoned prematurely in one patient because of life threatening haemorrhage. In the remaining two patients in whom treatment was unsuccessful bronchography had suggested very extensive endobronchial obstruction. Spirometry and radionuclide lung scans were performed before and after treatment in eight patients treated successfully and showed significant improvements. Four patients were investigated within two weeks of lung re-expansion by repeat bronchography (three patients) or computed tomography (one patient); in each case the calibre of the airways had returned almost to normal. Thus the radiological demonstration of bronchial dilation in a collapsed lung does not necessarily imply a diagnosis of irreversible bronchiectasis and should not be regarded as a contraindication to treatment. It is concluded that preoperative bronchography provides reliable data on the extent of tumour, the patency of the distal airways, and presence of extensive cavitation. This information should facilitate successful laser treatment.